ANTIBACTERIAL, ANTIOXIDANT ACTIVITIES AND MINERAL CONTENT FROM THE ALGERIAN MEDICINAL PLANTS - Hadjira Guenane; Omar Mechraoui; Boulanouar Bakchiche; Mebrouk Djedid; Abdelaziz Gherib; Mokhtar Benalia (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The present study evaluated the antioxidant and antibacterial activities of six aromatic plants, indigenous to the flora of the Algerian. The plants studied were Thymus vulgaris, Artemisia absinthium, scorzonena undulata, Malva Parviflora, Marrubium vulgare and Cotula cinerea. Extracts of these plants were analyzed for their total phenol compounds and antioxidant activity. The antimicrobial screening of the extracts was evaluated by agar disc diffusion method, the liquid broth microdilution was used to determine the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). Essential oil of A. absinthium possesses highest antioxidant activity among all extracts tested and phenolic extract of T. Vulgaris highest of DPPH radical. Among the plants screened, essential oil of A. absinthium and T. Vulgaris phenolic extract showed the best antibacterial activity. The mineral contents were determined by an atomic absorption spectrophotometer. Ca, K, Na, Mg, Fe and Cu were found to be the most abundant elements among the plants studied.